African Agency and Colonial Committees at Fourah Bay College : Architecture and planning of the new Fourah Bay College in Freetown, Sierra Leone (Docomomo Journal, 2023)
Fourah Bay College was the first Western-style university to be established along the West African coast in 1827. Primarily used to train missionaries and traders operating in British West Africa, it remained one of the premier educational establishments, overlooking the docks of Cline Town in Freetown, Sierra Leone. Following the Colonial Development and Welfare Acts and civil unrest in the aftermath of World War II, British colonial policy began to fund a series of secondary and tertiary education institutions. Modeled on the new University of the West Indies, these new universities adopted the residential college dorm typology coupled with the latest modernist architecture designed to enhance climatic comfort.A new campus was proposed for Fourah Bay, and in contrast to earlier precedents, the architectural approach was to be more humble and less monumental. Following a masterplan by London-based architects Norman and Dawbarn, the much smaller and relatively unknown British practice of Frank Rutter was appointed to design most of the campus buildings. The centerpiece is a large concrete tower named after John F. Kennedy, symbolic of the shifting political posturing for control and influence. Following Independence in 1961 and with increasing technical aid offered to neighboring Ghana and Nigeria from Socialist Eastern European powers, Fourah Bay College demonstrated how these political attempts for influence were directly played out through these newly formed institutions. Fourah Bay College also reveals the African agency in appointing architects and who was able to control the procurement processes and design teams. Rutter was dismissed as ‘college architect’ by a small contingent of newly qualified Sierra Leonean architects eager to ensure local appointments and architectural expressions were given opportunity. The campus, with its impressive architectural structures and innovative solutions, mirrors the political flux and shifting global power structures of the late 1950s and early 1960s, along with the local agency of Freetown architects and their quest to shape the future.
Keywords: Sierra Leone; West Africa; Freetown; Tropical; Modernism